The Effect of Adjuvant Therapy on Metabolic Syndrome in Schizophrenia Patients at Madani Hospital - Kurnia Utami, Indah; Yasinta Rakanita; Patricia Novina Nurak; Niluh Puspita Dewi (Journal of Public Health and Pharmacy, 2024)
Background: Schizophrenia is a mental disorder that impacts behavior, emotions, and communication. In recent years, atypical antipsychotics have been increasingly prescribed because they significantly reduce both positive and negative symptoms. However, the long-term effects of atypical can cause metabolic syndrome. Additional therapy is provided to maximize the primary therapy and reduce the side effects. Method: This study used a quasi-experimental design with a single-blind, pretest-posttest approach. Patients who had been using atypical antipsychotics, either monotherapy or combination therapy, for more than 3 were examined pretest to determine metabolic syndrome levels. Group A received adjuvant therapy, while Group B did not receive adjuvant therapy. Based on this data, an analysis of the reduction in metabolic syndrome categories was conducted. Result: The percentage of schizophrenia patients by gender was dominated by males (60%). By age, the majority were adults (87%). In Group A, the incidence of metabolic syndrome decreased from 53% in the pretest to 40% in the posttest after being given vitamin A, B, and folic acid therapy. The most commonly used other medication was THP (38%). Conclusion: The administration of adjuvant therapy with vitamins A, B, E, and folic acid can reduce the value of one or two of the five metabolic syndrome criteria for schizophrenia patients (p = 0.052) compared to the group of patients who did not receive vitamins A, B, E, and folic acid adjuvant therapy. Future research should use a longer duration to observe the effects of vitamins A, B, E, and folic acid and evaluate their therapeutic doses. Additionally, it should narrow down the criteria for medication use, focusing solely on the atypical antipsychotic’s clozapine or olanzapine.